2005
DOI: 10.1002/jbm.a.30351
|View full text |Cite
|
Sign up to set email alerts
|

Performance of polyoxymethylene plastic (POM) as a component of a tissue engineering bioreactor

Abstract: Polyoxymethylene (POM, acetal homopolymer, polyacetal), commercialized as Delrin by DuPont, is an engineering resin with mechanical properties that make it useful for the prototyping and manufacture of laboratory apparatus. These properties include excellent, "metal-like," machining characteristics and dimensional stability, as well as thermal stability, which allows steam sterilization. Historically, POM has been used widely, including as a surgical implant material. For these reasons, we have used this plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…This tissue restraint is composed of nylon mesh adhered to an acetal homopolymer thermoplastic ring. This polymer is used in tissue-engineering bioreactors and surgical implants, chosen for its machining characteristics, strength, and thermal stability that renders it innocuous (Penick, Solchaga, Berilla, & Welter, 2005). The nylon mesh faces the sensor probes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This tissue restraint is composed of nylon mesh adhered to an acetal homopolymer thermoplastic ring. This polymer is used in tissue-engineering bioreactors and surgical implants, chosen for its machining characteristics, strength, and thermal stability that renders it innocuous (Penick, Solchaga, Berilla, & Welter, 2005). The nylon mesh faces the sensor probes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…POM as a media-wetted component in a tissue-engineering bioreactor was applied by Penick et al [10] who found that the use of POM appears to be innocuous, at least with respect to human mesenchymal stem cells (MSC)-based tissue engineering, even after machining and repeated autoclaving.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that acetal resin inhibited both colony formation and growth of hematopoietic stem cells, whether it was in direct contact with the cells or in indirect contact by conditioning media. Penick et al23 concluded that the use of acetal resin as a culture medium‐wetted component appears to be innocuous, at least for human MSCs. The acetal resin samples were steam‐autoclaved 1 to 20 times, to assess the possibility of any toxic thermal breakdown product release into the media.…”
Section: Discussionmentioning
confidence: 99%